2015
DOI: 10.5152/tpd.2015.3608
|View full text |Cite
|
Sign up to set email alerts
|

Amoebic Liver Abscess in a Patient Initially Diagnosed with Pneumonia: Case Report and Discussion of Relevant Literature

Abstract: In one-third of the patients with amoebiasis, amoebic liver abscess (ALA) may occur after the penetration of amoebic trophozoites through the intestinal wall. ALA is seen mostly among men aged 20-45 years with a serious clinical outcome, with fever and abdominal pain on the right upper quadrant. Most patients have no recent history of amoebic colitis; indeed, they have neither gastrointestinal complaints nor Entamoeba histolytica (E. histolytica) cysts/trophozoites in their stools. Therefore, ultrasonography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In a study, trichrome-stained 49 smear samples of 51 patients were found positive for E. histolytica/dispar at clinics of the Ege University Hospital in the Izmir province of the Aegean region, Turkey (407). A case of amoebic liver abscess caused by penetration of amoebic trophozoites of E. histolytica was diagnosed at the clinics of a university hospital in the Istanbul province (408).…”
Section: Zoonotic Parasitic Protozoans (Protozooses)mentioning
confidence: 99%
“…In a study, trichrome-stained 49 smear samples of 51 patients were found positive for E. histolytica/dispar at clinics of the Ege University Hospital in the Izmir province of the Aegean region, Turkey (407). A case of amoebic liver abscess caused by penetration of amoebic trophozoites of E. histolytica was diagnosed at the clinics of a university hospital in the Istanbul province (408).…”
Section: Zoonotic Parasitic Protozoans (Protozooses)mentioning
confidence: 99%